Role of circulating sphingolipids in lipid metabolism: Why dietary lipids matter - Calzada, Catherine; Vors, Cécile; Penhoat, Armelle; Cheillan, David; Michalski, Marie-Caroline (Frontiers in Nutrition, 2023)
Sphingolipids are structural components of cell membranes and lipoproteins but also act as signalling molecules in many pathophysiological processes. Although sphingolipids comprise a small part of the plasma lipidome, some plasma sphingolipids are recognized as implicated in the development of metabolic diseases and cardiovascular diseases. Plasma sphingolipids are mostly carried out into lipoproteins and may modulate their functional properties. Lipids ingested from the diet contribute to the plasma lipid pool besides lipids produced by the liver and released from the adipose tissue. Depending on their source, quality and quantity, dietary lipids may modulate sphingolipids both in plasma and lipoproteins. A few human dietary intervention studies investigated the impact of dietary lipids on circulating sphingolipids and lipid-related cardiovascular risk markers. On the one hand, dietary saturated fatty acids, mainly palmitic acid, may increase ceramide concentrations in plasma, triglyceride-rich lipoproteins and HDL. On the other hand, milk polar lipids may decrease some molecular species of sphingomyelins and ceramides in plasma and intestine-derived chylomicrons. Altogether, dietary lipids can modulate circulating sphingolipids, lipid metabolism and possibly cardiovascular health.